AB0664 Off Label Biologic Therapy in a Cohort of Patients with Behçet Disease. (9th June 2015) - Monti, S.; Todoerti, M.; Cavagna, L.; Codullo, V.; Montecucco, C.; Caporali, R.
Abstract : Background: The treatment of Behçet disease (BD) is still largely based on the evidence driven from few randomized controlled trials (RCTs), case series and off label use of biologic agents (1). Objectives: To determine disease characteristics and treatment strategies, with particular focus on the indications, outcomes and safety of biologic therapy, in a cohort of patients with BD. Methods: Patients with a diagnosis of BD were recorded in a database since diagnosis and followed until the latest follow up visit, analyzing disease flares and therapeutic strategies adopted. All patients provided written informed consent. Results: A total of 79 patients were included. General characteristics of the study population are presented in table 1 . The most frequent disease manifestations were mucosal (100%), cutaneous (67.09%) and musculoskeletal involvement (62.02%). 11 patients (13.9%) were treated with biologic agents. All patients experienced non-biologic therapy before starting a TNF-inhibitor (TNFi) agent. The preferred first-line TNFi was infliximab (n=6), followed by adalimumab (n=3) and etanercept (n=1). The most frequent indications for biologic step up therapy were untreatable mucosal ulcers and arthritis (n=6), neurological involvement (n=2), refractory uveitis (n=1) and intestinal involvement (n=1). Most patients initiated a biological treatment within the first year of follow up. TNFi were more frequently prescribed in combination with methotrexate or azathioprine. 7 patients switched to a second TNFi (adalimumab n=4, infliximab n=2, or etanercept n=1) because of inefficacy of the first biologic agent (n=6) or safety issues (recurrent infections; n=1). The main reason for switching to a different biologic agent was refractory arthritis and mucocutaneous involvement. Only 1 patient was treated with three different TNFi because of a particularly aggressive musculoskeletal involvement. Rituximab (500 mg prescribed once a week for 4 infusions to be repeated after at least 6 months) was successfully used in one patient with recurrent pancytopenia, allowing complete and long-standing remission after 8 therapeutic cycles. The off label prescription of biologic agents did not raise any safety or tolerability issues in our cohort of BD patients and allowed for a 90.91% remission rate by the time of the latest follow up visit. Conclusions: A relevant proportion of patients in our BD cohort required to be treated with biological agents, mainly because of mucocutaneous, musculoskeletal or neurological disease manifestations. Off label use of biologic agents was generally effective and safe. Further studies are needed to define a dedicated and patient-tailored therapeutic approach. References: Hatemi G, Silman A, Bang D, Bodaghi B, Chamberlain AM, et al. Management of Behçet disease: a systematic literature review for the European League Against Rheumatism evidence-based recommendations for the management of Behçet disease. Ann Rheum Dis 2009;68(10):1528-34 Disclosure of Interest: None declared